"I'm Not Your 'Typical' Military Wife": The Construction of Gender and Agency Through Stereotypes. Issue 3 (July 2020) - Ziff, Elizabeth; Garland-Jackson, Felicia
Within the institution and military community, civilian wives of service members occupy complicated roles. On the one hand, wives are undisputedly crucial to the functioning of their service member husbands. However, wives are simultaneously considered subordinate to their husbands within the military and extended community. Indicative of this attitude are the divisive stereotypes of military wives that range from lazy and irresponsible, to overly rank-conscious and entitled. Based on combined in-depth interviews from two samples of military wives, this article investigates how the women navigate the military spouse role within the institutional, community-oriented context of the military. Specifically, we ask, how do these women construct gender and exercise agency when drawing on the stereotypes of wives within the community? By utilizing such mechanisms as symbolic boundary work, gender policing, and stereotyping, women both reify stereotypes of the military spouse and exert agency in creating the military spouse identity for themselves.